One gene, two proteins: coordinated production of a copper chaperone by differential transcript formation and translational frameshifting in Escherichia coli. Issue 4 (6th October 2017) - Drees, Steffen L.; Klinkert, Birgit; Helling, Stefan; Beyer, Dominik F.; Marcus, Katrin; Narberhaus, Franz; Lübben, Mathias
Summary: Programmed ribosomal frameshifting (PRF) is a translational anomaly causing the ribosome to shift into an alternative reading frame. PRFs are common in viral genomes, using a single nucleotide sequence to code for two proteins in overlapping frames. In bacteria and eukaryota, PRFs are less frequent. We report on a PRF in the copper detoxification system of Escherichia coli where a metallochaperone is generated out of the first 69 amino acids and a C‐terminal out‐of‐frame glycine of the gene copA . copA besides codes for the P1B ‐ATPase CopA, a membrane‐integral protein and principal interaction target of the chaperone. To enhance the production of the frameshift‐generated cytosolic copper binding protein a truncated transcript is produced from the monocistronic copA gene. This shorter transcript is essential for producing sufficient amounts of the chaperone to support the membrane pump. The findings close the gap in our understanding of the molecular physiology of cytoplasmic copper transport in E. coli, revealing that a chaperone‐like entity is required for full functionality of the P1B ‐ATPase copper pump. We, moreover, demonstrate that the primary transcriptional response to copper results in formation of the small transcript and concurrently, the metallochaperone plays a key role in resistance against copper shock. Abstract : A copper chaperone is formed by a highly efficient translational frameshift mechanism in Escherichia coli out of the initial region of copA, a gene encoding a copper export pump. In presence of copper, an additional transcript much shorter and more stable than the copA mRNA is formed, which drives the synthesis of increased amounts of the chaperone. The chaperone is, moreover, shown to be involved in defense against copper shock.